GAMBARAN PENGETAHUAN MENYIKAT GIGI PADA IBU PKK DI WILAYAH RT 07 DESA BANYUAJUH, KECAMATAN KAMAL - Riska Safitri Suhardi; Sri Hidayati; Soesilaningtyas Soesilaningtyas (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Palembang, 2022)
Background: Brushing teeth is one of the easiest things that can be done to maintain dental health. Brushing the wrong teeth continuously can lead to poor dental hygiene resulting in tooth decay such as dental caries (dental cavities) / calculus (tartar). Dental hygiene can be calculated by OHI-S which consists of the sum of DI (Debris Index) and CI (Calculus Index). High OHI-S can cause diseases that can damage tooth structure such as gingivitis. The problem of this research is the high percentage of OHI-S in PKK RT 7 Banyuajuh Village, Kamal District. Objective: This objective was to determine knowledge about brushing teeth among PKK RT 7 women, Banyuajuh Village, Kamal District, which included knowledge about the purpose of brushing teeth, knowledge about how to brush teeth, knowledge about the frequency and time of brushing teeth, and knowledge about the selection of toothpaste and toothbrush. Methods: This research is descriptive by involving 40 PKK RT 7 mothers as respondents. Data collection was obtained through a questionnaire. Results: The results showed that the knowledge of how to brush teeth in PKK RT 7, Banyuajuh Village, Kamal District was in the sufficient category.